2009
DOI: 10.1002/jmv.21570
|View full text |Cite
|
Sign up to set email alerts
|

Response to pegylated interferon alfa‐2a and ribavirin in chronic hepatitis C genotype 4

Abstract: The safety and efficacy of pegylated interferon (PEG-IFN) alfa-2a and ribavirin were studied among patients treated for genotype 4 chronic hepatitis C. Ninety-five patients with chronic hepatitis C genotype 4 were treated with PEG-IFN alfa-2a (180 microg/week) plus ribavirin (> or =11 mg/kg/day) for 48 weeks. The primary end point was sustained virological response, defined as non-detectable levels of HCV RNA at the end of follow up (week 72). The proportion with sustained virological response was 58/95 = 61.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…It is likely that the Ala43Thr polymorphism arose spontaneously in Asians/Japanese after the human ancestor population separated into Caucasians and Asians in the early history of Man. The current study found that NR have higher viral load and higher grade of liver activity and fibrosis than in responders but with no significant differences which agree with previous studies on HCV genotype-4 [24,25]. On the contrary, several studies have shown that high viral load and high grade of liver activity and fibrosis are negatively related with sustained virological response to interferon treatment [26,27].…”
Section: Pathway ''B''supporting
confidence: 80%
“…It is likely that the Ala43Thr polymorphism arose spontaneously in Asians/Japanese after the human ancestor population separated into Caucasians and Asians in the early history of Man. The current study found that NR have higher viral load and higher grade of liver activity and fibrosis than in responders but with no significant differences which agree with previous studies on HCV genotype-4 [24,25]. On the contrary, several studies have shown that high viral load and high grade of liver activity and fibrosis are negatively related with sustained virological response to interferon treatment [26,27].…”
Section: Pathway ''B''supporting
confidence: 80%
“…Data for the efficacy of standard combination therapy with Peg-IFNα plus ribavirin in genotype 4 comes mainly from endemic areas such as Egypt [8,9,12,14], Saudi Arabia [10], Kuwait [13] and Quatar [11]. The reported SVRs range between 59.7 and 67.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the efficacy of current combination therapy with pegylated interferon-α (Peg-IFNα) plus weight-based ribavirin is limited and contradictory; sustained virological response (SVR) rates of more than 60% reported in endemic areas [8][9][10][11][12][13][14] are approximately two times higher than those encountered in Europe [15][16][17]. In Greece, genotype 4 accounts for about 15% of all HCV infections [18][19][20][21][22] and is generally considered as "difficult to treat" in everyday clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…These agents yield sustained virologic response (SVR) rates of about 40-45% in patients with genotype 1 and 75-80% in patients with genotypes 2 and 3. Patients with genotypes 4, 5, and 6 have SVR rates between these ranges [4,5]. Although the prevalence of the various genotypes varies according to ethnicity, race, and geography [6], the vast majority of patients worldwide are infected with HCV genotype 1 and fail to achieve SVR with the currently available therapy.…”
Section: Introductionmentioning
confidence: 99%